O lugar de fala na comunicação midiática contra o sexismo: ambivalência discursiva e política - Gripp, Phillipp Dias (2020)
This thesis defends the conception that a subject can assume places of speech by himself and/or together with others, positioning himself socially in situations of communication, from his identity adscriptions and within the scope of predetermined semiotic-discursive practices. The promotional media discourse against sexism of the HeForShe campaign, developed by UN Women and televised by the GNT channel, is investigated in order to analyze how subjects are invited to exercise a place of speech with another. The proposal is guided by the justification of deepening the debate on the notion of places of speech in studies of Communication. It is also guided by the recognition of how a subject is invited to assume a place of speech with another in the discursive production about the campaign. The empirical material is the audiovisual productions broadcast by GNT since the campaign joined the channel, in addition to other audiovisual texts that contextualize HeForShe. It starts with a theoretical framework that aims to encompass the notion of places of speech through the articulation between the concepts of discourse and identity in the scenario of power relations and link it to the relational scope of communication. Then, places of speech are understood as enunciation strategies that relate the subject's discourse to the assumed identity. The debate is problematized by showing the situation of a subject talking together with another through the alterity movement. The theoretical argument emphasizes that the notion of places of speech has an ambivalence: the discursive-post-structuralist and the political-representational. Furthermore, it presents a contextualization about gender studies that aims to highlight visionary feminism as a loving political movement and opposed to the perspective of hatred towards men. The methodological development is based on a structuring of discursive semiotics to examine the empirical material from the relationships that the texts contract with their context (paratextual level); with other texts that precede or follow them (syntagmatic intertextual level); and internally with the content and expression plans (intratextual level). The paratextual analysis of socio-historical and enunciative contextualization is divided into two dimensions: 1) the broad one, which recognizes the HeForShe campaign as directed to the fight against sexism and gender equality and guided by the objective of inviting men to position themselves favorably to the cause; and 2) the restricted one, which refers to the history and socio-cultural configuration of the GNT television channel. Intertextuality highlights information about the production of promotional audiovisual texts broadcast by GNT. Meanwhile, through the intratextuality are carried out the analysis of the expression plan and content of the pieces. It is possible to verify the viability of a subject being invited and assuming places of speech with others in situations of communication made visible by the GNT channel through the recognition of their identity adscriptions, through the alterity movement and being linked to the discursive-post-structuralist property.